2017
DOI: 10.1051/0004-6361/201525886
|View full text |Cite
|
Sign up to set email alerts
|

A grid of MARCS model atmospheres for late-type stars

Abstract: S-type stars are late-type giants whose atmospheres are enriched in carbon and s-process elements because of either extrinsic pollution by a binary companion or intrinsic nucleosynthesis and dredge-up on the thermally-pulsing asymptotic giant branch. A grid of MARCS model atmospheres has been computed for S stars, covering the range 2700 ≤ T eff (K) ≤ 4000, 0.50 ≤ C/O ≤ 0.99, 0 ≤ log g ≤ 5, [Fe/H] = 0., −0.5 dex, and [s/Fe] = 0, 1, and 2 dex (where the latter quantity refers to the global overabundance of s-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 62 publications
(72 reference statements)
3
41
0
Order By: Relevance
“…The atmospheric parameters {T eff , log g, [Fe/H], C/O, [s/Fe]}, where [s/Fe] 1 is the s-process enhancement with respect to the (metallicity-scaled) solar s-process contribution, were derived as in S18. In summary, this method performs a χ 2 adjustment between a grid of S-star MARCS synthetic spectra (Van Eck et al 2017) and observed HERMES spectra within carefully selected spectral regions, also considering synthetic and observed photometric color indices. Luminosity was calculated using the distances derived from the Gaia DR2 parallaxes, the reddening E B−V (retrieved from Gontcharov 2012) and the bolometric correction in the K-band as computed from the MARCS model atmospheres.…”
Section: Stellar Parameter Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The atmospheric parameters {T eff , log g, [Fe/H], C/O, [s/Fe]}, where [s/Fe] 1 is the s-process enhancement with respect to the (metallicity-scaled) solar s-process contribution, were derived as in S18. In summary, this method performs a χ 2 adjustment between a grid of S-star MARCS synthetic spectra (Van Eck et al 2017) and observed HERMES spectra within carefully selected spectral regions, also considering synthetic and observed photometric color indices. Luminosity was calculated using the distances derived from the Gaia DR2 parallaxes, the reddening E B−V (retrieved from Gontcharov 2012) and the bolometric correction in the K-band as computed from the MARCS model atmospheres.…”
Section: Stellar Parameter Determinationmentioning
confidence: 99%
“…As a complement to Van Eck et al (2017), we give here details about the exact meaning of the [s/Fe] parameter in the MARCS grid of S stars, which provides models with [s/Fe] = 0, +1, and +2 dex. This parameter adjusts the abundances log X for elements from Ga to Bi in the following way: X s = log 10 (n X /n H ) × 10 [Fe/H] × 10 [s/Fe] × f X,s , X r = log 10 (n X /n H ) × 10 [Fe/H] × 10 [r/Fe] × (1 − f X,s ) , log X = log 10 (10 X s + 10 X r ).…”
Section: Appendix A: [S/fe] In the Marcs Gridmentioning
confidence: 99%
“…Helling & Lucas 2009;Witte et al 2009;Crossfield et al 2013;Hu & Seager 2014;Morley et al 2017) or by changing the carbon-to-oxygen ratio (e.g. Madhusudhan et al 2011;Madhusudhan 2012;Helling et al 2017;Van Eck et al 2017). Gaidos (2000) was one of the earliest works suggesting the importance of C/O in an exoplanet context.…”
Section: Introductionmentioning
confidence: 99%
“…Three major schools are: (i) use of law of mass action and molecular equilibrium constants based on Gibbs free energy data (Tsuji 1973;Stock 2008;Bilger et al 2013), (ii) use of law of mass action and molecular equilibrium constants based on partition functions (Allard & Hauschildt 1995;Gustafsson et al 2008;Barklem & Collet 2016;Van Eck et al 2017), and (iii) minimisation of the system Gibbs free energy (Lodders 2003;Ackerman & Marley 2001;Miller-Ricci et al 2009;Mbarek & Kempton 2016;Blecic et al 2016). Helling et al (2008) provide a summary of approaches used in brown dwarf and planetary atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present an extension of the Marcs code (Gustafsson 1971;Jørgensen et al 1992;Gustafsson et al 2008; Article number, page 1 of 17 arXiv:1708.06976v1 [astro-ph.SR] 23 Aug 2017 Van Eck et al 2017) that has so far been used extensively for modeling atmospheres of cool stars (Lambert et al 1986;Plez 1992;Aringer et al 1997), including abundance analysis (e.g. Blackwell et al (1995); Matrozis et al (2013); Nissen et al (2014); Hill et al (2016); Siqueira-Mello et al (2016)), H 2 O detections (Ryde et al 2002;Aringer et al 2002), microdiamonds in carbon stars (Andersen & Jørgensen 1995), and instrument calibration (Decin et al 2003;Decin & Eriksson 2007).…”
Section: Introductionmentioning
confidence: 99%